Effects of Rational-Emotive Health Education Program on HIV risk perceptions among in-school adolescents in Nigeria. Issue 29 (July 2016) - Onyechi, Kay Chinonyelum Nwamaka; Eseadi, Chiedu; Okere, Anthony U.; Otu, Mkpoikanke Sunday
Abstract : Abstract: Exploring beliefs about personal risk for human immunodeficiency virus (HIV) infection is essential to understanding what motivates people to engage in behaviors that reduce or increase their risk of HIV infection. Therefore, the current study's objective was to examine the effects of a Rational-Emotive Health Education Program (REHEP) on HIV risk perceptions among in-school adolescents in Anambra State, Nigeria. Forty-four participants were identified as having high-risk perceptions about HIV infection through a self-report questionnaire and met the inclusion criteria. The treatment process was guided by a REHEP manual and consisted of 8 weeks of full intervention and 2 weeks of follow-up meetings that marked the end of intervention. The study used repeated measures analysis of variance to assess improvements in individual participants and across control and treatment group risk perceptions after the intervention. HIV risk perceptions of in-school adolescents did not differ across the treatment and control groups at baseline. Through REHEP, HIV risk perceptions significantly reduced in the treatment group compared to those in the control group. REHEP had significant effect on HIV risk perceptions of in-school adolescents exposed to treatment group, despite their sex. Religious background did not determine the significant effect of REHEP on HIV risk perceptions of in-school adolescents in the treatment group. Follow-up studies that would use a REHEP to assist client population from other parts of the country to promote HIV risk reduction, especially among those with high-risk behavior, are needed in Nigeria.